The Relationship of Professional Commitment of Auditing Student and Anticipatory Socialization toward Whistleblowing Intention. (31st May 2016) - Mela, Nanda Fito; Zarefar, Arumega; Andreas
Abstract: The purpose of this research is to obtain the empirical evidence about the influence of professional commitment of auditing student and anticipatory socialization to the whistleblowing intention in Pekanbaru. This research population is all students who have taken auditing subject and the entire population chosen as research sample. Data were analysed by multiple regression using SPSS software. A total of 69 questionnaires distributed to students - students who have taken auditing in Pekanbaru, and the 52 questionnaires that can be processed (75%). The results indicated professional commitment of auditing student impact on whistleblowing intention. While no effect on the anticipatory socialization to whistleblowing intention.